Enantiopurity analysis of new types of acyclic nucleoside phosphonates by capillary electrophoresis with cyclodextrins as chiral selectors - Solínová, Veronika; Kaiser, Martin Maxmilián; Lukáč, Miloš; Janeba, Zlatko; Kašička, Václav (Journal of separation science, 2014)
CE methods have been developed for the chiral analysis of new types of six acyclic nucleoside phosphonates, nucleotide analogs bearing [(3-hydroxypropan-2-yl)-1H-1,2,3-triazol-4-yl]phosphonic acid, 2-[(diisopropoxyphosphonyl)methoxy]propanoic acid, or 2-(phosphonomethoxy)propanoic acid moieties attached to adenine, guanine, 2,6-diaminopurine, uracil, and 5-bromouracil nucleobases, using neutral and cationic cyclodextrins as chiral selectors. With the exception of the 5-bromouracil-derived acyclic nucleoside phosphonate with a 2-(phosphonomethoxy)propanoic acid side chain, the R and S enantiomers of the other five acyclic nucleoside phosphonates were successfully separated with sufficient resolutions, 1.51-2.94, within a reasonable time, 13-28 min, by CE in alkaline BGEs (50 mM sodium tetraborate adjusted with NaOH to pH 9.60, 9.85, and 10.30, respectively) containing 20 mg/mL β-cyclodextrin as the chiral selector. A baseline separation of the R and S enantiomers of the 5-bromouracil-derived acyclic nucleoside phosphonate with 2-(phosphonomethoxy)propanoic acid side chain was achieved within a short time of 7 min by CE in an acidic BGE (20:40 mM Tris/phosphate, pH 2.20) using 60 mg/mL quaternary ammonium β-cyclodextrin chiral selector. The developed methods were applied for the assessment of the enantiomeric purity of the above acyclic nucleoside phosphonates. The preparations of all these compounds were found to be synthesized in pure enantiomeric forms. Using UV absorption detection at 206 nm, their concentration detection limits were in the low micromolar range.
Keywords: cyklodextriny; molekulární struktura; CE; Cyclodextrins; Molecular Structure; Nucleosides; Cyclodextrins / Nucleotide analogs; nukleosidy; Acyclic nucleoside phosphonates; Electrophoresis, Capillary; stereoizomerie; Organophosphonates; elektroforéza kapilární; organofosfonáty; Stereoisomerism; Chiral analysis